Influence of biological markers on overall survival in surgically treated patients with non-small cell lung cancer - Lončarević, Olivera; Lončarević, Slobodan; Vekić, Berislav; Djukanović, Leonida; Vuković, Jelena; Rančić, Nemanja (Vojnosanitetski pregled, 2021)
Background/Aim. Non-small cell lung cancer (NSCLC) is one of the most common malignant tumors and a leading cause of cancer-related deaths. The aim of this study was to assess the impact of biological markers on the overall survival rate in surgically treated NSCLC patients who received adjuvant chemotherapy and/or radiation therapy. Methods. This retrospective case series study included patients with NSCLC treated in the period between 2008 and 2017 at the Pulmonology Clinic and the Clinic for Chest Surgery, Military Medical Academy, Belgrade, Serbia. The survival analysis performed was based on immunohistological findings, histology type, and tumor, node, metastasis (TNM) stages. Results. The mortality rate was higher in the adenocarcinoma patient group compared to the squamous cell carcinoma group, albeit without statistical significance (58.3% vs. 31.2%, respectively; p = 0.175). Overall survival was shorter in the adenocarcinoma patient group compared to the squamous cell carcinoma group by approximately 750 days. Likewise, overall survival was shorter in the adenocarcinoma patient group compared to the squamous cell carcinoma group for CD31 positive (p = 0.029), p-63 positive (p = 0.049), MMP-9 positive (p = 0.032), and matrix metalloproteinase (MMP)-2 positive patients (p = 0.016). Conclusion. Adenocarcinoma is a more aggressive cancer type compared to squamous cell carcinoma with shorter overall survival. Our research showed a poorer overall survival in the adenocarcinoma group of patients compared to the squamous cell carcinoma group in CD31, p-63, MMP-9, and MMP-2 positive patients.
Keywords: biomarkers; carcinoma, non-small-cell lung; immunohistochemistry; survival; neoplasm staging; surgical procedures, operative